Analysis of Factors Influencing in Social Entrepreneurial Intention : An Empirical Study of Students in Purworejo Regency, Indonesia - Srimaryani Srimaryani; Siswandari Siswandari; E. Muhtar (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to analyze the factors that affect social entrepreneurial intentions in Purworejo Regency, particularly among university students. Social entrepreneurship is perceived as a potential solution to address economic inequality, unemployment, and poverty, issues worsened by the Covid-19 pandemic. Data shows that Purworejo Regency has high levels of poverty and unemployment, while the number of entrepreneurs is still low. This study used a quantitative approach with a survey method of 113 students from three universities. The research instrument used was a questionnaire designed based on the research framework, distributed online via Google Form, where respondents completed closed-ended questions using a rating scale. To analyze the data, descriptive statistics were utilized, followed by correlation and multiple regression analyses conducted using IBM SPSS 25 to examine the relationships among the identified variables. Validity and reliability tests were performed to ensure the quality of the questionnaire items before hypothesis testing. The results showed that four variables empathy (EMP), self-efficacy (SE), previous experience with social issues (PEE), and entrepreneurship education (EE) had a positive and significant effect on social entrepreneurial intention (SEI), while moral obligation (MO) and perceived social support (PSS) were rejected as predictors. Specifically, empathy and self-efficacy were identified as strong predictors with significance levels less than 0.001, while PEE and EE also demonstrated significant effects with p-values of 0.008 and 0.002, respectively. This study highlights the importance of developing entrepreneurship education and support for students to increase social entrepreneurship intention in Purworejo Regency.